454 DIRECT DEMONSTRATION OF AN ANTI-INFLAMMATORY EFFECT OF SIMVASTATIN THERAPY IN THE METABOLIC SYNDROME. (1st January 2005) - Chan, E.; Devaraj, S.; Jialal, I.
Abstract : Inflammation plays a pivotal role in all stages of atherosclerosis. C-reactive protein (CRP), in addition to being a cardiovascular risk marker, may participate in atherothrombosis. Hydroxymethylglutaryl coenzyme A (HMG Co-A) reductase inhibitors (statins) have documented a reduction in cardiovascular events in clinical trials. In addition to their beneficial effects on the lipoprotein profile, they lower CRP levels. The metabolic syndrome (MS) is a proinflammatory state with a constellation of risk factors that predict the development of cardiovascular disease. There is a paucity of data examining the effect of statins on inflammation in MS. Hence, the aim of this study was to test the effect of simvastatin (40mg/day, S-40) on inflammatory markers, namely hsCRP and monocytic cytokines (TNF-α, IL-6 and IL-1b) in patients with MS defined by NCEP-ATPIII in a randomized, double-blind, placebo (P) - controlled study over 8 weeks. HsCRP levels were assayed using a high sensitivity near infra red particle rate immunoassay. Monocytes were separated by negative magnetic separation and activated with lipopolysaccharide (LPS, 100 ng/mL) in presence and absence of mevalonate (250μM) and monocyte cytokines were assayed by sandwich ELISA. The coefficient of variation of the hsCRP and monocyte cytokine assays were ≤10%. There were no differences in age, gender, BMI, lipoprotein levels and inflammatory markers in the two groups at baseline. As expected, S-40 therapy resulted in a significant lowering of LDL cholesterol levels at both 4 and 8 weeks compared to placebo (34% reduction at 8 weeks, p≤0.0005). S-40 therapy also significantly decreased hsCRP levels at 4 and 8 weeks compared to placebo (36% median reduction at 8 weeks, p≤0.0005). Furthermore S-40 therapy compared to placebo resulted in a significant reduction in LPS-activated monocytic release of IL-6 and TNF at both 4 and 8 weeks (% median reduction at 8 weeks for IL-6 and TNF 55% and 39% respectively, p≤0.025). S-40 therapy failed to affect monocyte IL-1b release. In addition to there being no correlation between LDL cholesterol reduction and CRP reduction with S-40, co-incubation of monocytes with mevalonate did not reverse the inhibition of IL-6 and TNF seen with S-40. Thus, we show, for the first time, a direct anti-inflammatory effect of S-40 therapy on hsCRP and monocyte IL-6 and TNF in patients with MS. This has major implications in forestalling cardiovascular disease in this high risk group.